Analysis of Energy Transport Behavior and Geometric Effects in Graphene - Guajardo-Cuéllar, Alejandro; Go, David B.; Sen, Mihir (Frontiers in Mechanical Engineering, 2020)
Graphene is an excellent heat conductor, with the potential to be used as a heat spreader for applications where there are fast, transient heat pulses. In this study we analyze and describe energy transport in graphene subject to an initial pulse of energy. We analyze the effects of using harmonic, anharmonic, and a non-linear (Tersoff) potentials to describe the transient energy transport and compare these to classical continuum descriptions. The energy pulse produces pure wave-like behavior and a spatial energy distribution that has geometric features similar to the graphene geometry itself. Depending on the potential used, the energy travels outward from the impulse location following a similar pattern as the hexagonal shape of graphene. This pattern is clearly identified when the transport is treated with a harmonic potential. Increasing the anharmonicity and non-linearity dampens this effect and results in thermal transport that does not follow the geometry of graphene.